A bibliometric analysis of H. J. Eysenck's research output: Clarifying controversy. (1st February 2021) - Andersen, Njål; Corr, Philip J.; Furnham, Adrian
Abstract: We present a bibliometric analysis of a large corpus of research work by H. J. Eysenck (1916–1997), who was one of the most famous and productive psychologists of the 20th century. It utilizes new bibliometric tools to update an analysis of Rushton (2001), examining how articles cluster in terms of themes and co-authors. We present our analysis in the light of a recent investigation by King's College London, which concluded that a number of Eysenck's papers are 'unsafe' and they recommended that journal editors should consider their retraction. We enquire about the relationship between these personality and fatal disease papers and the wider body of Eysenck's work. Our analysis revealed that these papers are part of a research topic that stands apart from his many other seminal contributions to psychological knowledge; and, even if they were all retracted, this would have little impact on the main corpus of his work. Our analysis and presentation shines a new light on the contribution of Britain's most productive, but sometimes controversial, psychologist.